2017
DOI: 10.1177/0269215517730669
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative psychosocial factors predicting patient’s functional recovery after total knee or total hip arthroplasty: a systematic review

Abstract: Overall, the results of this systematic review suggest that there is no longitudinal association between preoperative psychosocial factors and perceived or observed patient's postoperative functional recovery after total joint arthroplasty. The psychological category mental well-being is related to observed postoperative recovery >6 weeks through ≤3 months and to change score after total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…One such study showed that patients' participation in their hospital care facilitated pain management and consequently their satisfaction [36]. Another study of expectations and experiences regarding sports activities among elderly TKA patients concluded that in order for counseling on sports activities after joint replacement to be perceived as supportive, it was important to consider individual motives, barriers, and previous sports experience [4]. Similarly, other qualitative studies showed the importance of patient participation, education, and information for satisfaction after TKA surgery [23,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…One such study showed that patients' participation in their hospital care facilitated pain management and consequently their satisfaction [36]. Another study of expectations and experiences regarding sports activities among elderly TKA patients concluded that in order for counseling on sports activities after joint replacement to be perceived as supportive, it was important to consider individual motives, barriers, and previous sports experience [4]. Similarly, other qualitative studies showed the importance of patient participation, education, and information for satisfaction after TKA surgery [23,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Although the surgery is successful for many patients, 10-30% of patients experience long-term pain and functional limitations after surgery 4,5 . To optimise outcomes, there has been increasing interest in identifying prognostic factors for a poor outcome after joint replacement [6][7][8][9][10] . Identification of prognostic factors could facilitate the provision of stratified care and optimise outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no studies directly investigating the impact of psychological factors on TKR, but prior studies primarily focused on influence of psychological factors on pain and function after TKR. Preoperative psychological factors have been identified as important risk factors for poor outcome in patients undergoing TKR [30,31]. A recent systematic review including 17 cohort studies concluded that psychological factors are predictive of poor clinical outcomes including patients' satisfaction, pain or function after TKR [32].…”
Section: Discussionmentioning
confidence: 99%